Efficacy of single‐balloon overtube for endoscopic submucosal dissection in the proximal colon: A propensity score‐matched analysis - Hidenori Tanaka; Shiro Oka; Akiyoshi Tsuboi; Yuki Kamigaichi; Hirosato Tamari; Akihiko Sumioka; Yasutsugu Shimohara; Tomoyuki Nishimura; Katsuaki Inagaki; Yuki Okamoto; Sumio Iio; Ken Yamashita; et al. (DEN Open, 2022)
Abstract Objectives A single‐balloon overtube (SBO) can improve poor scope operability during colonic endoscopic submucosal dissection (ESD). We aimed to evaluate the clinical usefulness of SBO for ESD in the proximal colon and the predictive factors for cases in which SBO is useful. Methods A total of 88 tumors located in the proximal colon resected by balloon‐assisted ESD (BA‐ESD) using SBO and 461 tumors resected by conventional ESD (C‐ESD) between June 2015 and November 2020 were considered. Seventy‐eight tumors each in the BA‐ESD and C‐ESD groups were matched by propensity score matching. ESD outcomes were compared between the groups, and a decision tree analysis was performed to explore the predictive factors for cases in which SBO is useful. Results There were no significant differences between the groups in the major outcomes such as en bloc resection rate (95% vs. 99%, p = 0.17), R0 resection rate (92% vs. 96%, p = 0.30), mean dissection speed (16 mm2/min vs. 16 mm2/min, p = 0.53), and intraoperative perforation rate (5% vs. 6%, p = 0.73). Even when considering cases with poor preoperative scope operability, there were no significant differences between the groups. Comparison of tumors ≥40 mm in diameter between the groups confirmed that the intraoperative perforation rate was significantly lower in the BA‐ESD group than in the C‐ESD group (0% vs. 24%, p = 0.0188). Conclusion SBO is useful for ESD of tumors ≥40 mm in diameter in the proximal colon to prevent intraoperative perforation, which usually has a long procedure time.